Facial mask and Meaw technique in a class III patient managing. Case report - Quintana, Rubén; Díaz, Luis-Fernando; Bedoya, Antonio (Revista Estomatología, 2015)
The management of Class III malocclusion involves several considerations to be taken at the time of making therapeutic decisions, such as age, sex, the technique used, general conditions of the patient, collaboration and aesthetic requirements. This is a malocclusion that demands quick and effective action to ensure aesthetic and functional conditions as a priority. This report presents a case of a 14 years with a skeletal Class III malocclusion treated initially with facial mask and Mc .Namara breaker, in order to make a posteroanterior protraction of the maxilla and the mandible sagital control, then continue with the technique of MEAW multi-ansas, thus achieves a dentoalveolar compensation and better occlusal adjustment.